Rückkehr zum Begriff "Erwachsenenbildung"? - Siebert, Horst [Verfasser] (My University, 1988)
"The controversy concerning the terms 'adult education' and 'continuing education' has quite a long history. The last term rather refers to a 'systemfunctional' political and economic interest of planning, whereas 'adult education' rather points to an anthropological founded, undivided concept of education. The author pleads for the usage of the term 'adult education'. In the presence of the predominant interest in a 'technocratic' based further education the necessity of an up-to-date clarification regarding the terms 'education' and 'adult' is emphasized in the article." (author's abstract ; BIBB-Doku)
Keywords: Erwachsenenbildung; Berufliche Weiterbildung; Fachsprache